A study of inguinal hernia in children - Kumar, Rakesh; Prasad, Vijay Shankar (International Surgery Journal, 2018)
Background: Inguinoscrotal swellings are one of the commonest anomalies in infancy and childhood throughout the world. Delay in diagnosis and treatment leads to loss of testis, ovaries or portion of bowel to incarceration or strangulation. This study was undertaken to evaluate the age, sex and sidewise distribution and the complications like incarceration, strangulation and gonadal infarction. Methods: A total of 50 children were selected ranging in age from new born to 12 years presenting with inguinoscrotal swelling which were examined, followed up and managed. Results: The inguinal hernia was most common among male children (92%) thereby giving a ratio of M: F=11.5:1. The children were aged new born -12 years and most of the patients presented around 2 to 7(46%) years and prematurity noticed in 10% of cases. Right sided (64%) inguinal hernia was more common than left (28%). In this study indirect hernia is 98% and direct is 2%. In 16 cases of hydrocele, 10 were on the left side and 6 were on the right and 6 cases were encysted hydrocele. High ligation at the level of deep ring was done in all the cases. In this series of 50 children, there were 2 cases of incarceration. But none had strangulation and gonadal infarction. Conclusions: Inguinal hernia is a common surgical condition in children. Elective surgery is associated with minimal complications. Incarceration is more common in infancy with chances of recurrence if explored in emergency.